Microeconomic Theory According to Abu Ubayd And Al-Shaibani - Moh. Asep Zakariya Ansori; Yadi Janwari; Ahmad Hasan Ridwan (al-Afkar, Journal For Islamic Studies, 2023)
This study aims to analyze the microeconomic theory according to Abu Ubayd in his book entitled Al-Amwal and Al-Syaibâni in his book entitled Al-Kasb. The research method used is descriptive qualitative with content analysis techniques obtained from both books. Abu Ubayd in Kitab al-Amwal explains various aspects of microeconomics in the management of public finance or commonly called state assets, such as taxation, zakat, law, as well as administrative law and international law. Meanwhile, Al-Syaibâni in Al-Kasb discusses microeconomic studies that revolve around the theory of al-kasb (income) and its sources as well as guidelines for production and consumption behavior. The conclusion of this study is that the thoughts of Abu Ubayd and al-Syaibâni contributed greatly to the development of economics, especially in the sub-field of microeconomics. Further studies can be conducted to compare their views with other modern theories to identify which aspects are still relevant today